Catalytic oxidation of ethyl acetate over La-Co and La-Cu oxides - X. Chen (2014)
Lanthanum-containing mixed oxides (La-Co and La-Cu) were synthesized by several methods: exotemplating, evaporation, glycine-nitrate and glycine-nitrate-exotemplating. Samples were characterized by thermogravimetry and differential scanning calorimetry, N2 adsorption, temperature programmed reduction, scanning electron microscopy and X-ray diffraction. The materials obtained were tested as catalysts for ethyl acetate oxidation, as a model volatile organic compound. La-Cu samples showed poor catalytic performance, but La-Co materials were much more active than the individual components. Catalytic activity seems to be mainly determined by the easiness of reduction of the catalysts, which is related to the availability of oxygen from the lattice. Catalysts containing Co or Cu in excess of La (on a molar base) were more active than the corresponding mixed oxides consisting of equal amounts of La and the transition metal. Samples prepared by the evaporation method were more active than those prepared by exotemplating, for the same molar ratio. Samples prepared by evaporation and glycine-nitrate methods calcined at 600°C had a better performance than the corresponding oxides calcined at 300°C. The most active sample found in this study was the La-Co mixed oxide prepared by the glycine nitrate method and calcined at 600°C, 100% conversion of ethyl acetate to H2O and CO2 being achieved at 230°C.